新加坡庙宇灵签典故研究 = A study of the divination slips in Singapore Chinese temples - 杜馨慧 Toh, Xin Hui (2010)
In contemporary Singapore society, temple oracle slips are regarded as highly important to devotees; despite the fact that it has been a traditional custom and seen as deities’ advice to the devotees. Socially, temple oracle slips have the ability to calm the minds of the people. Culturally, temple oracle slips allow the young and old alike to come into contact with traditional literary studies revealed in the slips. This study focuses on various aspects of temple oracle slips which I have collected from various communal and historical temples in Singapore. As such research has not previously conducted in Singapore; this thesis will be a pioneer study and research effort in this area. The scope of the thesis consists of five chapters. Chapter One describes the motive, aim and the methods use for this study while Chapter Two introduces the history and the development of temple oracle slips. In Chapter Three, analysis and comparison of the oracle slips will be carried out from various literature works of the chosen temple oracle slips found in both communal and historical temples. Chapter Four concludes this study with an analysis on current cultural oracle phenomenon, the significance of cultural and literary tales contained in temple oracle slips and attempts to point out the disturbing fact that this cultural artifact are also slowly fading away.